2006
DOI: 10.1002/chin.200629014
|View full text |Cite
|
Sign up to set email alerts
|

Ag/AgBr/TiO2 Visible Light Photocatalyst for Destruction of Azodyes and Bacteria.

Abstract: was prepared by the deposition-precipitation method and was found to be a novel visible light driven photocatalyst. The catalyst showed high efficiency for the degradation of nonbiodegradable azodyes and the killing of Escherichia coli under visible light irradiation (λ > 420 nm). The catalyst activity was maintained effectively after successive cyclic experiments under UV or visible light irradiation without the destruction of AgBr. On the basis of the characterization of X-ray diffraction, X-ray photoelectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
99
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(103 citation statements)
references
References 7 publications
4
99
0
Order By: Relevance
“…Because of these properties, silver halides have not been studied much in photocatalytic reactions. Recently, we have reported that the novel visiblelight-driven photocatalyst AgBr/TiO2 shows high efficiency in the degradation of nonbiodegradable azodyes and the killing of Escherichia coli under visible light irradiation (12). Our results indicate that AgBr is the main photoactive species for the destruction of pollutants under visible light.…”
Section: Introductionmentioning
confidence: 66%
“…Because of these properties, silver halides have not been studied much in photocatalytic reactions. Recently, we have reported that the novel visiblelight-driven photocatalyst AgBr/TiO2 shows high efficiency in the degradation of nonbiodegradable azodyes and the killing of Escherichia coli under visible light irradiation (12). Our results indicate that AgBr is the main photoactive species for the destruction of pollutants under visible light.…”
Section: Introductionmentioning
confidence: 66%
“…Afterward, Huang et al [20] found that the modification of TiO 2 with Ag/AgCl obviously improved its photocatalytic activity. However, previous research has mainly focused on the fabrication of nano-sized Ag/AgCl/TiO 2 catalysts, such as nanoparticles [21,22], nanospheres [23], nanoarrays [20,24] and nanofibers [25]. These nano-sized catalysts are difficult to separate directly Figure 1a,c,e, the surface of TF is homogeneous and smooth, while the surface of CTF and S-CTF are rough.…”
Section: Introductionmentioning
confidence: 99%
“…It has been known that during the fi rst minutes bacteria use self-defence and auto-repair mechanisms to protect against the active species generated under irradiation. Oxidation of outer membrane begins gradually but not suffi ciently to cause serious damage to the Unauthenticated Download Date | 5/10/18 6:35 PM bacterial cells 22 . It was assumed that better antibacterial properties presented photocatalyst characterized by similar anatase and rutile crystallite sizes.…”
Section: Discussionmentioning
confidence: 99%